2008
DOI: 10.1007/s11695-008-9606-8
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Arrest After Intragastric Balloon Insertion in a Super-Obese Patient

Abstract: A super-obese patient who suffered from severe sleep apnea (SSA) and other comorbidities underwent insertion of a BioEnterics intragastric balloon (BIB) before bariatric surgery. During the night, he was victim of cardiac arrest. After cardiopulmonary resuscitation and return of spontaneous circulation, he was transferred to intensive care unit. Two hours later, he developed an unexpected symptomatic bradycardia, and BIB was removed. The patient had no further cardiac complications, but he had a poor neurologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 17 publications
0
11
0
2
Order By: Relevance
“…Perforation of the esophagus was reported by Nijhof et al [17] after balloon insertion and balloon extraction by Ruiz et al [18]. In one report of cardiac arrest [19] after BIB® implantation in a super-obese patient, the patient developed unexpected nocturnal bradycardia resulting in cardiopulmonary resuscitation and removal of the balloon. It was assumed that BIB® induced vagal nerve stimulation by gastric wallstretching.…”
Section: Discussionmentioning
confidence: 94%
“…Perforation of the esophagus was reported by Nijhof et al [17] after balloon insertion and balloon extraction by Ruiz et al [18]. In one report of cardiac arrest [19] after BIB® implantation in a super-obese patient, the patient developed unexpected nocturnal bradycardia resulting in cardiopulmonary resuscitation and removal of the balloon. It was assumed that BIB® induced vagal nerve stimulation by gastric wallstretching.…”
Section: Discussionmentioning
confidence: 94%
“…La perte de l'excès de poids à la fin du traitement était de 32,1 % en moyenne avec une perte de poids variant de 10 à 19 kg en moyenne en quatre à six mois selon les études [7][8][9][10][11][12][13][14][15][16] et la réduction moyenne de l'indice de masse corporelle (IMC) de 5,7 kg/m 2 . Cependant, malgré l'importance du nombre de sujets perdus de vue, une part importante de la perte d'excès de poids pourrait être reprise un an après la fin du traitement.…”
Section: Discussionunclassified
“…Des perforations oesophagiennes ont été décrites suite à des difficultés de pose [11] ou d'extraction [12] du BIG. Cubattoli et al [13] ont décrit un cas d'arrêt cardiaque se compliquant d'un état végétatif, par probable stimulation vagale quelques heures après la pose d'un BIG.…”
Section: Discussionunclassified
“…It has many merits such as outpatient application, reversibility, re-applicability, lower rates of gastrointestinal and systemic complications, and decreased food consummation [1,4,6,10,11]. The IGB has been also used as preparation for major surgical procedures to minimize anesthesia risk [6], and it has been indicated that it can be safely applied in morbidly obese patients before bariatric procedures to decrease morbidity and mortality following definitive surgery [12,13]. Left hepatic lobe volume decrease facilitates the laparoscopic procedures [3].…”
Section: Discussionmentioning
confidence: 99%